THE USE OF SHARED READING TECHNIQUE TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 KANDIS OGAN ILIR - Rachmanita (Language and Education Journal, 2016)
One needs to be proficient in each of the four language skills namely, listening, speaking, reading, and writing in order to become a well rounded communicator. However, the ability to read skillfully, provide students with several distinct advantages. By having sufficient reading skill, students will make a better progress and development in learning English. In other words, students who want to be good in English must be able to read well and students who can comprehend the text not only will get much knowledge but also will obtain many vocabularies as well. Therefore, the aim of this study was to find out whether shared reading technique could improve students’ reading skill achievement or not. Quasi experimental method and non-randomized control group control group pre-test and post test design were used in this study. The population was the eighth grade students of SMP Negeri 1 Kandis Ogan Ilir in the academic year of 2014/2015 with total number of 172 students. There were two groups taken as the sample and each group consisted of thirty students. The data were collected by using writing test in the form of multiple choice. The data obtained were analyzed by using t-test. The findings showed that shared reading technique could improve students’ reading achievement.